PENGARUH DOSIS PUPUK KASGOT DAN PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI KERITING (Capsicum annum L.) DALAM POLYBAG - Maulana, Alsa Putra; Pamungkas, Djoko Heru; Setiawati, Evi (Universitas Sarjanawiyata Tamansiswa, 2025)
The research aimed to determine the effect of kasgot fertilizer dosage and NPK fertilizer on the growth and yield of curly chili plants (Capsicum annum L.) in polibag which was carried out from October to January 2024, located in the garden of “Tumuju Guyub” Blunyahrejo Yogyakarta, Tegal Rejo District, Yogyakarta City, Yogyakarta Special Region. This research was carried out with 3 replications using a Complete Randomized Group Design (RAKL) with two factors of kasgot fertilizer and NPK , there were 9 treatment combinations, each combination was repeated 3 times so as to obtain 27 experimental units consisting of 5 plants and 3 plants were sampled so that the total was 135 plants. K1 (100 g/polibag kasgot dose), K2 (150 g/polibag kasgot dose), K3 (200 g/polibag kasgot dose), P1 (10 g/polibag npk dose), P2 (15 g/polibag npk dose), P3 (20 g/polibag npk dose). observation variables include plant height, number of leaves, root wet weight, root length, plant fresh weight, plant dry weight, root dry weight, marketable weight, unsaleable weight, fruit weight per-hectare. Observation data using analysis of sources of variance (ANOVA) and Analysis is done using Duncan's Multiple Range Test (DMRT) at the level of α = 5%. Based on the results of the analysis, by giving the dose treatment of pukuk kasgot and npk does not affect the growth and yield of curly chili plants.